2021
DOI: 10.3389/fpsyg.2021.775204
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress in Hospitals During the First Wave of the COVID-19 Pandemic: A Web-Based Survey Among 3,293 Healthcare Workers Within the German Network University Medicine

Abstract: Objective: The present study aimed to investigate the correlation between moral distress and mental health symptoms, socio-demographic, occupational, and COVID-19-related variables, and to determine differences in healthcare workers’ (HCW) moral distress during the first wave of the COVID-19 pandemic.Method: Data from 3,293 HCW from a web-based survey conducted between the 20th of April and the 5th of July 2020 were analyzed. We focused on moral distress (Moral Distress Thermometer, MDT), depressive symptoms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
4
19
3
1
Order By: Relevance
“…Our study, like prior studies of moral distress during the COVID-19 pandemic, found strong links between degree of exposure to COVID-19 (and its consequences) and moral distress [ 13 , 14 , 16 , 19 , 25 ]. Health care workers who have high levels of exposure or risk of death from COVID-19 believe that the pandemic makes it difficult for them to provide optimal patient care because of fear of being infected or dying from COVID-19 [ 44 ].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our study, like prior studies of moral distress during the COVID-19 pandemic, found strong links between degree of exposure to COVID-19 (and its consequences) and moral distress [ 13 , 14 , 16 , 19 , 25 ]. Health care workers who have high levels of exposure or risk of death from COVID-19 believe that the pandemic makes it difficult for them to provide optimal patient care because of fear of being infected or dying from COVID-19 [ 44 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, the intensity (severity) of moral distress among health workers during the pandemic, in those studies that reported mean moral distress levels, has been found to be low in most [ 11 , 13 21 ] though not all [ 22 24 ] studies. Among these studies, some assessed the intensity of moral distress for specific situations [ 15 , 20 ], some assessed both the frequency and intensity of moral distress for specific situations [ 13 , 14 , 17 , 18 , 21 , 22 , 24 , 25 ] and others assessed it with a global measure of moral distress without anchoring the assessment to specific potentially-morally-distressing situations [ 11 , 19 , 23 ]. The systematic reviews by Gianetta and colleagues [ 1 ] and by Tian and colleagues [ 26 ] provide comprehensive discussions of instruments that have been used to measure moral distress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 2 The changes we have seen may be in place long-term and it is therefore important to understand the impact on doctors and to investigate the ways in which they are adapting and coping. Previous literature has explored the experiences of healthcare workers across a broad range of settings during the pandemic 3 , 4 and the impact of mask wearing on communication. 5 Studies in palliative care have shown an increase in anxiety and psychological distress amongst healthcare workers, 6 and a struggle to communicate and connect effectively with patients due to work pressures and national restrictions.…”
Section: Introductionmentioning
confidence: 99%